2015
DOI: 10.1111/jace.13648
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of Highly Transparent Yttria Ceramics with Fine Microstructures by a Hot‐Pressing Method

Abstract: In this study, we report highly transparent yttria ceramics fabricated by a facile hot‐pressing method with tantalum foil shielding which effectively prevents the ceramic samples from carbon contamination caused by the graphite mold used during the process. The hot‐pressed sample was already highly transparent without a post‐annealing step or hot isostatic pressing. For a 2‐mm‐thick specimen doped with 1 at.% ZrO2, the in‐line transmittance reaches 74.4% at 400 nm and 81.1% at 1100 nm. The sample shows a very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…ICP analysis indicated that SiO 2 impurity was introduced from BN powders and graphite gaskets which were used as isolation materials during the sintering process. It can be eliminated by using high‐purity isolation materials like tantalum foil . The intense absorption around 7 μm and weak absorption at 11.4 μm correspond to the C–H vibration absorption.…”
Section: Resultsmentioning
confidence: 99%
“…ICP analysis indicated that SiO 2 impurity was introduced from BN powders and graphite gaskets which were used as isolation materials during the sintering process. It can be eliminated by using high‐purity isolation materials like tantalum foil . The intense absorption around 7 μm and weak absorption at 11.4 μm correspond to the C–H vibration absorption.…”
Section: Resultsmentioning
confidence: 99%
“…The details of the hot-pressing process were reported in our previously published paper. 13 After the hot-pressing process, the samples were annealed at 1200°C for 2 h in air and then HIPed under a pressure of 180 MPa at 1450°C for 5 h in an argon atmosphere. Finally, the samples were annealed again at 1200°C for 2 h in air.…”
Section: Methodsmentioning
confidence: 99%
“…Optically transparent yttria has many advantages, such as high melting temperature (2430°C), high corrosion resistance, broad transparency range (0.2‐10 μm), and high thermal conductivity [13.6 W·(m·K) −1 ] . The recent research and reports have shown the fabrication method of transparent yttria via hot pressing, vacuum sintering and hot isostatic pressing (HIP) for superior optical properties . There have also been many studies on the synthesis of yttria powder with high sinterability and the improvement of the transmittance according to the powder characteristics …”
Section: Introductionmentioning
confidence: 99%
“…The representative additive ion is Zr 4+ , and it has been studied for its inhibition of grain growth on transparent Y 2 O 3. The addition of the other tetravalent ions such as Ti 4+ and Hf 4+ on Y 2 O 3 also contributes to the inhibition of grin growth, which enhances the elimination of pores . To achieve almost fully dense ceramics, the interparticle pores need to be removed while the grain growth is suppressed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation